2003
DOI: 10.1093/emboj/cdg107
|View full text |Cite
|
Sign up to set email alerts
|

A role for N-glycanase in the cytosolic turnover of glycoproteins

Abstract: Successful maturation determines the intracellular fate of secretory and membrane proteins in the endoplasmic reticulum (ER). Failure of proteins to fold or assemble properly can lead to their retention in the ER and redirects them to the cytosol for degradation by the proteasome. Proteasome inhibitors can yield deglycosylated cytoplasmic intermediates that are the result of an N-glycanase activity, believed to act prior to destruction of these substrates by the proteasome. A gene encoding a yeast peptide:N-gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
192
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(199 citation statements)
references
References 48 publications
6
192
1
Order By: Relevance
“…One model suggests that N-glycans are re-glucosylated only if positioned close to the folding defect. 21 Again, because the terminals of a polypeptide chain may be relatively easier to be unfolded, UGT1 bound on the terminal N-glycan could detect the uncovered hydrophobic patches more often and resend the protein into the folding cycle in ER. Further studies will be needed to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…One model suggests that N-glycans are re-glucosylated only if positioned close to the folding defect. 21 Again, because the terminals of a polypeptide chain may be relatively easier to be unfolded, UGT1 bound on the terminal N-glycan could detect the uncovered hydrophobic patches more often and resend the protein into the folding cycle in ER. Further studies will be needed to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Peptide-N-glycanase (PNGase) catalyzes the deglycosylation of several misfolded N-linked glycoproteins (2,3) by cleaving the bulky glycan chain before the proteins are degraded by the proteasome (4). PNGase is highly conserved in eukaryotes and possesses a catalytic Cys, His, and Asp triad embedded in a transglutaminase fold.…”
mentioning
confidence: 99%
“…Moreover, recent studies revealed that PNGase specifically acts on the unfolded form of high-mannose type N-glycosylated proteins (4,12,13). However, how PNGase binds to glycan chains and how it recognizes the high-mannose type substrates is unknown.…”
mentioning
confidence: 99%
“…Misfolded N-linked glycoproteins destined for degradation are recognized by a highly conserved deglycosylating enzyme, peptide:N-glycanase (PNGase), implicated in proteasomal degradation (4). Very recent findings established that PNGase acts upstream of the proteasome and facilitates subsequent degradation of misfolded N-linked glycoproteins by deglycosylating them (5,6).…”
mentioning
confidence: 99%